2020
DOI: 10.1115/1.4048348
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh–Taylor Instability With Varying Periods of Zero Acceleration

Abstract: We present our findings from a numerical investigation of the acceleration-driven Rayleigh-Taylor Instability, modulated by varying periods without an applied acceleration field. It is well known from studies on shock-driven Richtmyer-Meshkov instability that mixing without external forcing grows with a scaling exponent as ~ t^{0.20-0.28}. When the Rayleigh-Taylor Instability is subjected to varying periods of "zero" acceleration, the structural changes to the mixing layer remain remarkably small. After the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Limited attention has been given to experimental RTI studies that have coupled physics that may affect instability growth. These include (a) the coupled shear-buoyancy problem where RTI and KHI are competing [101], [113], and [133]; (b) the tilted rig RTI problem where the tilt gives rise to an angled (two-dimensional) interface concerning an acceleration history due to rockets (as in RR) attached at the top of the tank [69,71]; (c) suppression of RTI due to rotational effects [134,135]; (d) RTI with variable acceleration history [49,75,76,[136][137][138]; (e) RTI in solids where the material strength needs to be overcome before the growth of the instability [139][140][141]; and (f) compressible RTI in cylindrical geometry [142]. RTI experiments are extremely difficult to build, operate, run, and diagnose; as a result, the number of experimental studies pales in comparison to computational and modeling efforts.…”
Section: Conclusion and Some Future Opportunitiesmentioning
confidence: 99%
“…Limited attention has been given to experimental RTI studies that have coupled physics that may affect instability growth. These include (a) the coupled shear-buoyancy problem where RTI and KHI are competing [101], [113], and [133]; (b) the tilted rig RTI problem where the tilt gives rise to an angled (two-dimensional) interface concerning an acceleration history due to rockets (as in RR) attached at the top of the tank [69,71]; (c) suppression of RTI due to rotational effects [134,135]; (d) RTI with variable acceleration history [49,75,76,[136][137][138]; (e) RTI in solids where the material strength needs to be overcome before the growth of the instability [139][140][141]; and (f) compressible RTI in cylindrical geometry [142]. RTI experiments are extremely difficult to build, operate, run, and diagnose; as a result, the number of experimental studies pales in comparison to computational and modeling efforts.…”
Section: Conclusion and Some Future Opportunitiesmentioning
confidence: 99%
“…We have formulated a set of generalized, scale resolving (SR) variables for variable density turbulence, b, a i , T i j , in equations (29)(30)(31), which are presented and discussed in section II. These variables are written as inner products of the fluctuations of a quantity q of the form qi (x) ≡ q i (ξ ) − u i (x),…”
Section: Discussionmentioning
confidence: 99%
“…Aslangil et al [25], [12] discuss how the identification of these regimes makes it possible to draw parallels between HVDT and more complex VDT flows, such as Rayleigh-Taylor Instability (RTI) 26,27 , RTI under variable-acceleration [28][29][30][31] , Richtmyer-Meshkov Instability (RMI) 32,33 , VD mixing layers 34 , and VD jets 35 , among others. Recent reviews of some of these flows and the relevant VD processes involved may be found in [31, 36, and 37].…”
Section: Flow Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aslangil et al explore RTI-induced mixing for zero acceleration with variable periods. The results were compared with the case of classical constant gravity, when acceleration is removed for either some indefinite period or intermediate period [79]. Sabet et al demonstrated that mixing properties of fluids influenced drastically due to viscosity contrast between two miscible fluids under the destabilization effect of RTI [80].…”
Section: Review Of the Current Statusmentioning
confidence: 99%